Pelaksanaan Jurnal Membaca Untuk Meningkatkan Literasi Baca Siswa Kelas 5 SD Takhassus Al-Qur'an - Dzawi Hizbatul Maola (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2025)
Early reading is the initial stage in developing literacy skills among elementary school students. The habit of reading quality texts plays a role in enhancing intelligence and critical thinking abilities. This study aims to: 1) examine the effectiveness of a reading journal program in improving reading interest among fifth-grade students at SD Takhassus Al-Qur’an Kalibeber Wonosobo, and 2) measure the extent of the improvement. The research used a quantitative approach with a quasi-experimental method, applying a pretest-posttest control group design. Data collection techniques included observation and questionnaires, while data analysis involved preliminary analysis and hypothesis testing through gain score analysis and the Mann–Whitney U test. The results showed that: 1) the reading journal program developed using Canva was implemented effectively; 2) there was a significant increase in reading literacy ability, with a gain score of 0.756, categorized as high; and 3) there was a significant difference between the experimental and control groups, indicated by the Mann–Whitney U test result in the experimental class (Sig. = 0.006 < 0.05). Thus, the reading journal program is proven to be effective in enhancing students’ reading literacy in Grade 5.